Astrocytes and Microglia in Stress-Induced Neuroinflammation: The African Perspective - Olude, Matthew Ayokunle; Mouihate, Abdeslam; Mustapha, Oluwaseun Ahmed; Farina, Cinthia; Quintana, Francisco Javier; Olopade, James Olukayode (Frontiers in Immunology, 2022)
Background: Africa is laden with a youthful population, vast mineral resources and rich fauna. However, decades of unfortunate historical, sociocultural and leadership challenges make the continent a hotspot for poverty, indoor and outdoor pollutants with attendant stress factors such as violence, malnutrition, infectious outbreaks and psychological perturbations. The burden of these stressors initiate neuroinflammatory responses but the pattern and mechanisms of glial activation in these scenarios are yet to be properly elucidated. Africa is therefore most vulnerable to neurological stressors when placed against a backdrop of demographics that favor explosive childbearing, a vast population of unemployed youths making up a projected 42% of global youth population by 2030, repressive sociocultural policies towards women, poor access to healthcare, malnutrition, rapid urbanization, climate change and pollution. Early life stress, whether physical or psychological, induces neuroinflammatory response in developing nervous system and consequently leads to the emergence of mental health problems during adulthood. Brain inflammatory response is driven largely by inflammatory mediators released by glial cells; namely astrocytes and microglia. These inflammatory mediators alter the developmental trajectory of fetal and neonatal brain and results in long-lasting maladaptive behaviors and cognitive deficits. This review seeks to highlight the patterns and mechanisms of stressors such as poverty, developmental stress, environmental pollutions as well as malnutrition stress on astrocytes and microglia in neuroinflammation within the African context.